Powering through the Storm : Climate Resilience for Energy Systems - Ramstein, Celine Sarah Marie; Schweikert, Amy; Ramstein, Celine; Nicolas, Claire (World Bank, Washington, DC, 2022)
Climate change and its impacts on power systems often mean more frequent power outages and repairs, which raise maintenance costs and pose other challenges. Yet proactive modifications in project design, maintenance, and operation can enhance system resilience at lower costs than reactive adaptation. This Live Wire considers the implications of climate resilience in the power sector and highlights ongoing World Bank work and best practice, with a focus on Africa.